Prenatal chromosomal microarray analysis in 2466 fetuses with ultrasonographic soft markers: a prospective cohort study - Hu, Ting; Tian, Tian; Zhang, Zhu; Wang, Jiamin; Hu, Rui; Xiao, Like; Zhu, Hongmei; Lai, Yi; Wang, He; Liu, Shanling (American journal of obstetrics and gynecology, 2021)
Soft markers are nonspecific findings detected by ultrasonography during the second trimester that are often transient and nonpathologic but may imply an increased risk of underlying fetal aneuploidy. However, large-scale prospectively stratified studies focusing on the prevalence of chromosomal aberrations, including copy number variants, in fetuses with different types of isolated soft markers have rarely been published in the literature. This study aimed to investigate clinical outcomes in fetuses with isolated soft markers by single nucleotide polymorphism array with long-term follow-up and to propose a diagnostic algorithm based on specific types of soft markers. The prevalence of fetal isolated soft markers was 13.2% (7869 of 59,503). A total of 2466 fetuses with ultrasonographic soft markers during the second trimester, which were subjected to single nucleotide polymorphism array with long-term follow-up, were selected in this prospective study over a 5-year period. Soft markers were categorized into 12 groups. The demographic profile and chromosomal microarray analysis detection results were analyzed and compared among different groups. The overall prevalence of chromosomal aberrations in fetuses with soft markers was 4.3% (107 of 2466), which comprised 40.2% with numeric chromosomal abnormalities, 48.6% with pathogenic copy number variants, and 11.2% with likely pathogenic copy number variants. The incidence of numeric chromosomal abnormalities was significantly higher in multiple soft markers (5.5% vs 1.5%; P=.001) and the thickened nuchal fold group (8.3% vs 1.7%; P=.024). Meanwhile, the incidence of pathogenic copy number variants was significantly higher in multiple soft markers (5.5% vs 2.4%; P=.046) and the short femur length group (6.6% vs 2.2%; P<.0001). The incidences of pathogenic copy number variants in fetuses with isolated echogenic intracardiac focus, enlarged cisterna magna, choroid plexus cysts, echogenic bowel, or single umbilical artery were lower than 1.5%. The normal infant rate in fetuses without chromosomal aberrations was 91.7%; however, it was significantly lower in the mild ventriculomegaly (86.2% vs 93.0%; P<.0001) and short femur length groups (71.4% vs 93.6%; P<.0001). The potential chromosomal aberrations and clinical prognoses varied widely among different types of isolated soft markers. Pathogenic copy number variants are more often present in specific soft markers, especially when multiple soft markers are found. Thus, a specific soft marker type–based prenatal genetic testing algorithm was proposed.